2011
DOI: 10.1007/s12288-011-0126-7
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Plasmacytoma: A Case Series and Review of the Literature

Abstract: Plasmacytomas are malignant proliferations of plasma cells which can occur with different plasma cell dyscrasias. Solitary plasmacytomas of bone or extraosseous plasmacytomas, depending on the tissue of origin, develop in isolation without systemic manifestations of multiple myeloma. Three cases of cranial plasmacytomas are described, two in patients with multiple myeloma and one extraosseous plasmacytoma. Management options are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Favorable response to radiotherapy is usually over 80%. [2,9] A R0 resection seems decisive in the presented cases. Even though both patients received postoperative radiotherapy, relapse was documented during follow-up of the patient with subtotal resection.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Favorable response to radiotherapy is usually over 80%. [2,9] A R0 resection seems decisive in the presented cases. Even though both patients received postoperative radiotherapy, relapse was documented during follow-up of the patient with subtotal resection.…”
Section: Discussionmentioning
confidence: 71%
“…After a bibliographical review of surgical resection of plasmacytomas, we found in an article from Na'ara et al A progression to MM from SBP has been established, thus chemotherapy should be initiated in patients in which this progression is documented. [2,9] During follow-up consultations of the presented patients, there was no progression to MM. Prognosis for SBP and EMP is better compared to MM.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the appropriate management of plasmacytomas associated with multiple myeloma is less definitive. Most authors suggest chemotherapy with radiation as the first line for these lesions, even when there is a mass effect, because of their exquisite sensitivity to this approach [ 9 - 10 ]. Surgical resection is typically reserved for those refractory to therapy or unable to receive radiation due to proximity to sensitive structures such as the optic chiasm.…”
Section: Discussionmentioning
confidence: 99%